2014
DOI: 10.5152/tjbh.2014.1914
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Methylene Blue in Sentinel Lymph Node Biopsy for Early Breast Cancer

Abstract: Objective: Sentinel lymph node biopsy is the recommended approach in the evaluation of axilla during breast cancer surgery. In this study, results of patients who underwent methylene blue sentinel lymph node biopsy were evaluated. Materials and Methods:The study included 32 female patients with T1 and T2 tumors. 5 ml of 1% methylene blue was injected into the peritumoral area or around the cavity. The axillary sentinel lymph node was found and removed, and then axillary dissection was performed. The sentinel l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…However, Ozdemir et al reported no such risks while using methylene blue dye. 30 In the study done by Fattahi et al, the demographic and histopathologic characteristics were not considerably different in patent blue dye group and methylene blue dye group. 32 All the patients had a mean tumour size of 2.4cm with standard deviation of 0.8cm.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, Ozdemir et al reported no such risks while using methylene blue dye. 30 In the study done by Fattahi et al, the demographic and histopathologic characteristics were not considerably different in patent blue dye group and methylene blue dye group. 32 All the patients had a mean tumour size of 2.4cm with standard deviation of 0.8cm.…”
Section: Discussionmentioning
confidence: 83%
“…In study done by Ozdemir et al, Isosulphane blue or methylene blue was injected in the first method. 30 Radioactive material was injected first, and the sentinel lymph node was found with a gamma probe in another method. This study suggests that these two methods can be used in combination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reports indicate identification rates (IR) as a point of success in the SLN mapping process 4 , although appropriate criteria for successful identification of a SLN is often missing. Clinical trials involving SLN mapping outline inclusion criteria for SLNs reported based on nodes that are only stained blue 2,8,23-28 , blue and non-blue nodes with dye uptake in afferent lymphatic channels 11,12,14,[29][30][31][32][33][34][35] , or do not comment on IR inclusion criteria [36][37][38] . The inconsistent or lack of standardized, objective reporting across SLN mapping trials and cases that utilize methylene blue skews accuracy and reduces comparability of results between studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, its side effects are less serious than isosulphane blue. 1,2 The limiting factor of MB is its poor penetration through the cell membranes and some allergic reactions. Radiopharmaceuticals have been used as an alternative or in addition to dyes for external imaging and/or radiation detector monitoring for the SLN detection and mapping before surgery.…”
Section: Introduction U N C O R R E C T E D P R O O Fmentioning
confidence: 99%